2023
DOI: 10.1080/21505594.2023.2280838
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and virulence of Shigella sonnei : A highly drug-resistant pathogen of increasing prevalence

Xosé M. Matanza,
Abigail Clements

Abstract: Shigella spp. are the causative agent of shigellosis (or bacillary dysentery), a diarrhoeal disease characterized for the bacterial invasion of gut epithelial cells. Among the 4 species included in the genus, Shigella flexneri is principally responsible for the disease in the developing world while Shigella sonnei is the main causative agent in high-income countries. Remarkably, as more countries improve their socioeconomic conditions, we observe an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 246 publications
0
3
0
Order By: Relevance
“…The secular trend of increase of S. sonnei relative weight in the aetiology of culture-confirmed shigellosis in Israel was driven by a decline in S. flexneri shigellosis incidence and is in line with a similar trend in countries undergoing economic development and improvements in sanitation and water quality [ 6 , 23 ]. It probably reflects the better adaptation of S. sonnei than S. flexneri to more restricted modes of transmission associated with specific S. sonnei determinants such as a unique O antigen, the presence of a capsule, a mechanism to displace other enteric bacteria, which all act in protection against environmental stresses [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The secular trend of increase of S. sonnei relative weight in the aetiology of culture-confirmed shigellosis in Israel was driven by a decline in S. flexneri shigellosis incidence and is in line with a similar trend in countries undergoing economic development and improvements in sanitation and water quality [ 6 , 23 ]. It probably reflects the better adaptation of S. sonnei than S. flexneri to more restricted modes of transmission associated with specific S. sonnei determinants such as a unique O antigen, the presence of a capsule, a mechanism to displace other enteric bacteria, which all act in protection against environmental stresses [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there are a number of differences between S. sonnei and S. flexneri [16], in the context of anti-bacterial activity, one of the key distinctions is the presence of a Type VI Secretion System (T6SS). A T6SS has been identified in S. sonnei but only remnants remain in S. flexneri (16).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst there are a number of differences between S. sonnei and S. flexneri [16], in the context of anti-bacterial activity, one of the key distinctions is the presence of a Type VI Secretion System (T6SS). A T6SS has been identified in S. sonnei but only remnants remain in S. flexneri (16). In one clinical isolate it has been demonstrated that this T6SS plays a key role in outcompeting S. flexneri during infection or in polymicrobial environments thus allowing S. sonnei to gain a competitive advantage [17].…”
Section: Introductionmentioning
confidence: 99%